INFLUÊNCIA DOS PADRÕES DE INTEGRAÇÃO ESPACIAL DA MALHA URBANA NA INSERÇÃO DE EDIFÍCIOS ALTOS EM UMA CIDADE MÉDIA - Gregoletto, Debora; Braga, Andrea da Costa (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The objective of this paper is to investigate if the patterns of spatial integration of the urban grid influence the insertion of tall buildings, of different heights, in the urban grid of a Brazilian medium-sized city. In the context of increasing urbanization and marked transformations in the space of Brazilian cities, urban densification and verticalization stand out. Tall buildings, products of the verticalization, are increasingly present in Brazilian cities, especially in medium-sized cities. The insertion of high-rise buildings in cities can be influenced by the spatial patterns of the urban fabric and the expectations of the target public as to the integration or segregation of their places of life and their daily practices. In order to reach the proposed objective, the city of Caxias do Sul-RS is chosen as a case study and the work is based on the Spatial Syntax along with tools of analysis in the Geographic Information System GIS - and information obtained through government agencies. The main results indicate that tall buildings with lower heights were more distributed throughout the system, while tall buildings with higher height were located on the more integrated roads or just a few steps routes.